Commodification of Religion: Disruption and Shallowing of Religious Values in the Digital Era - Fianto, Latif; Ghofur, M. Abdul (The Sunan Ampel Review of Political and Social Sciences, 2023)
The phenomenon of widespread and massive use of social media TikTok has changed the social order and even religious values in society. TikTok, which was originally used as a social media, quickly turned into a platform used for purposes such as political economy and religion. Religious activities distributed on social media experience disruption and shallowing of values, because these activities are carried out solely to pursue economic needs. This research aims to find out comprehensively and analytically the extent to which disruption and shallowing of religious values occur on TikTok social media. The method used in this research is a qualitative method using Clifford Greetz's Thick Description theory approach, where the theory focuses on studying the in-depth meaning of cultural symbols. This research data was obtained through documentary data collection techniques in the form of videos of lectures or religious preaching on TikTok social media. The research results show that the presence of social media and its rapidly growing use has encouraged the commodification of religion, where religion is constructed and reduced in such a way that religion that was originally sacred becomes profane. Religious preaching is not only driven and constructed by the interests of the religion itself but also by market interests so that spiritual values in religion become increasingly shallow and uprooted.